Jacksonia scoparia R. Br. Leaf Extracts Lack Antibacterial Activity and are Non-toxic in vitro - Mpala, Lindiwe Nomathemba; Chikowe, Getmore Rumbudzai; Cock, Ian E. (Pharmacognosy Communications)
Introduction: Due to the development of bacterial strains that are resistant to multiple antibiotics, the development of new antibiotic therapies has become a priority for medical research. Traditional plant medicines are important leads for the discovery of new therapies and the search for novel antibiotic plant-based treatments has received substantial recent attention. The family Fabaceae is widely used therapeutically in many areas of the world, including for the treatment of bacterial diseases. Despite this, many members of this family are yet to be examined extensively for therapeutic properties. The endemic Australian species Jacksonia scoparia R.Br. was screened for antibacterial activity in this study against a panel of bacterial pathogens. Materials and Methods: The growth inhibitory activity of J. scoparia leaf extracts against a panel of bacterial pathogens was investigated by disc diffusion assay. Toxicity was examined using the Artemia franciscana lethality assay (ALA). Results: The methanolic and aqueous J. scoparia leaf extracts were devoid of inhibitory activity against panels of gram-positive and gram-negative bacteria. The extracts were non-toxic following 24 hr exposure in the ALA assay. Conclusion: The J. scoparia leaf extracts lacked bacterial growth inhibitory activity. However, these extracts may have other therapeutic properties and testing against protozoa, fungi, virus and tumour cells is required.
Keywords: Fabaceae; Dogwood; Antibiotic resistance; Australian plant; Traditional medicine; Antibacterial activity; Medicinal plants; Toxicity